Effects of Emotional Labor and Job Stress on the Job Burnout of Apartment Management Entity in Korea - Sang – Im, Lee; Ha-Sung, Kong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to examine the relations of emotional labor, job stress, and job burnout of management office workers as apartment management entity. In the results of the analysis, first, in differences of job burnout according to sex, the women experienced more severe emotional labor than men, and there were significant differences in emotional labor, which had statistically positive(+) effects. Second, in differences of job burnout according to age group, the respondents in their 30~45 and the respondents in their 45~60 showed more severe job burnout than the respondents in their 60 or up, and there were significant differences in job burnout, which had statistically positive(+) effects. Third, in the results of regression analysis on the effects of emotional labor on the job burnout, the emotional labor had statistically-significantly positive(+) effects on the job burnout. Fourth, in the results of regression analysis on the effects of job stress on the job burnout, the emotional labor had statistically-significantly positive(+) effects on the job burnout. Lastly, in the results of regression analysis on the effects of emotional labor and job stress on the job burnout, the emotional labor had statistically-significantly positive(+) effects on the job burnout.